Post-intensive care syndrome (PICS) – complications after ICU stay: selected issues - Wojnar-Gruszka, Katarzyna; Wojtas, Katarzyna; Jędrocha, Karolina (Nursing Problems / Problemy Pielęgniarstwa, 2023)
Patient hospitalisation in an intensive care unit (ICU) as a result of critical illness may cause deficits and illness in physical, mental, and cognitive dimensions. Side effects referred to as post-intensive care syndrome (PICS) most often include fatigue, weakness, pain sensation, depressive symptoms, anxiety disorders, PTSD, delirium, attention, and memory deficits. PICS contributes to the patient’s inability to return to work, reduced quality of life, and functional disability. The aim of this paper was to introduce selected issues concerning nature of the PICS phenomenon, based on an analysis of the available literature. Studies confirm the occurrence of PICS with varying degrees of severity and duration of symptoms, conditioned by sociodemographic variables and the patient’s health status. Given the long-term consequences of PICS, there is a need for further study in this area to understand the challenges facing the patient and to sensitise the treatment team on the need to evaluate the patient’s condition.